Model of leadership characteristics in addressing construction challenges - Ngah Nasaruddin, Nur Ain (2019)
Failure of construction projects could be attributed from several challenges that emerged along the construction processes. These challenges are categorised as resources allocation, time, cost, quality, safety, project complexity, changes, uncertainties, and communication. It requires several approaches to handle these challenges and one of it is to have good quality of leadership that not rely on their authority. A study has shown that poor leadership contributed 67% to the project’s failure. Hence, this study was intended to develop relationship between leadership characteristics with construction challenges in avoiding project failure. This study was carried out based on quantitative approach that involved questionnaire survey using face-to-face technique with selected respondents at managerial level of G7 Contractor Company. The survey has resulted with 117 valid responses. Results from the survey analysis were applied to develop PLS-SEM relationship model which consisted of 43 leadership characteristics which are categorised into 4 groups and 9 construction challenges which is categorised into single group. The model was statistically validated with Goodness-of-Fit (GoF) value of 0.349 which is categorised as medium validating power. Based on the developed model, the most influential leadership characteristic group in handling the construction challenges is smart decision. While the most challenging construction challenges is safety management. To ensure that the model is applicable to the Malaysia construction industry, expert verification by selected construction experts was conducted and found that majority of the experts agreed on the model outcomes thus indicate that the model is suitable to the industry. Hence, it can be concluded that the study has uncovered the importance of leadership characteristics and its relationship with the construction challenges which fills the gap of study on Malaysia construction industry.